2016
DOI: 10.1073/pnas.1521916113
|View full text |Cite
|
Sign up to set email alerts
|

The Entner–Doudoroff pathway is an overlooked glycolytic route in cyanobacteria and plants

Abstract: Glucose degradation pathways are central for energy and carbon metabolism throughout all domains of life. They provide ATP, NAD(P)H, and biosynthetic precursors for amino acids, nucleotides, and fatty acids. It is general knowledge that cyanobacteria and plants oxidize carbohydrates via glycolysis [the Embden-Meyerhof-Parnas (EMP) pathway] and the oxidative pentose phosphate (OPP) pathway. However, we found that both possess a third, previously overlooked pathway of glucose breakdown: the Entner-Doudoroff (ED)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
191
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(212 citation statements)
references
References 42 publications
9
191
1
2
Order By: Relevance
“…These results are in agreement with earlier studies showing that the mRNA amount of ndbC follows circadian rhythm peaking in the dark together with genes involved in sugar catabolism (Kucho et al, 2005;Layana and Diambra, 2011) as well as in the beginning of heterotrophy (Lee et al, 2007). Conversely, 6-PG hydratase (IlvD), which belongs to the recently discovered Entner-Doudoroff pathway in cyanobacteria (Chen et al, 2016), was up-regulated in DndbC in LC (Table III) and might partially compensate for the down-regulation of EMP and OPP.…”
Section: Carbon Catabolism Is Down-regulated In the Absence Of Ndbcsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with earlier studies showing that the mRNA amount of ndbC follows circadian rhythm peaking in the dark together with genes involved in sugar catabolism (Kucho et al, 2005;Layana and Diambra, 2011) as well as in the beginning of heterotrophy (Lee et al, 2007). Conversely, 6-PG hydratase (IlvD), which belongs to the recently discovered Entner-Doudoroff pathway in cyanobacteria (Chen et al, 2016), was up-regulated in DndbC in LC (Table III) and might partially compensate for the down-regulation of EMP and OPP.…”
Section: Carbon Catabolism Is Down-regulated In the Absence Of Ndbcsupporting
confidence: 93%
“…6C). The up-regulated Entner-Doudoroff pathway in DndbC (in LC), which is physiologically significant under mixotrophy (Chen et al, 2016), also could contribute to carbon flux distribution in the cells. Nevertheless, similar problems were present in cell division, as demonstrated in autotrophic conditions (Supplemental Fig.…”
Section: Ndbc Is Indispensable In Lahg Conditionsmentioning
confidence: 99%
“…Previous studies identified some unique presence/absence patterns for core metabolic genes in both Prochlorococcus and Synechococcus and relative to other cyanobacteria. For example, both have replaced the cyanobacterial RuBisCO and related proteins of the CO2-concentrating mechanism with proteobacterial variants (17)(18)(19), lost key genes in the cyanobacterial TCA cycle (20) and glycolysis (21), and acquired a menaquinone-based malate dehydrogenase (22). Photorespiration proteins are, in turn, universally preserved in Synechococcus, but unevenly distributed across Prochlorococcus ecotypes (9,23).…”
Section: Resultsmentioning
confidence: 99%
“…The two main metabolic routes which provide the cell with acetyl-CoA are CO 2 fixation through the Calvin-Benson-Bessham cycle (CBB) or degradation of glycogen through various pathways (Xiong et al, 2015; Chen et al, 2016). The biggest differences in acetyl-CoA pools were visible in the first 48 h of growth.…”
Section: Discussionmentioning
confidence: 99%